Pelatihan Pengelolaan Sumber Daya Manusia dan Penggunaan Media Digital untuk Pemasaran Produk Kain Tenun Khas Toraja pada Sentra Tenun UNNONI - Mey Enggane Limbongan; Dian Intan Tangkeallo; Althon K. Pongtuluran; Isak Pasulu’; Astriwari Biringkanae; Lisa Kurniasari Wibisono (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
Toraja woven fabric is a significant cultural heritage of the Indonesian archipelago, known for its high artistic value and immense potential as a regional leading product. Despite this, challenges remain, particularly in terms of human resource management, which tends to be relatively simple, and the limited use of digital media in marketing. To address these issues, a Community Service Program (PKM) was implemented with the goal of enhancing the human resource capacity at the UNNONI Weaving Center, as well as expanding its marketing reach through the utilization of digital media. The methods employed in the program included identifying the core problems, providing HR management training, conducting digital marketing workshops (focusing on social media and online marketplaces), mentoring, and evaluating the program’s outcomes. The HR management training emphasized improving business management, task distribution, production recording, and enhancing teamwork. The digital marketing training covered the creation of social media accounts, content creation using Canva, branding strategies, and utilizing online marketplaces for promotion. The results indicated a significant improvement in both management and marketing aspects. The HR at the weaving center began implementing more organized production records, work coordination improved, and the UNNONI social media accounts became actively used for promotional purposes. Additionally, the Shopee marketplace was utilized, allowing consumers from outside the region to purchase products. These results demonstrate the successful integration of traditional craftsmanship with modern digital tools to enhance business sustainability and reach